2018
DOI: 10.1637/11886-042718-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Are Microneutralization and Hemagglutination Inhibition Assays Comparable? Serological Results from Influenza Experimentally Infected Mallard Ducks

Abstract: The hemagglutination inhibition (HI) assay is commonly used to assess the humoral immune response against influenza A viruses (IAV). However, the microneutralization (MN) assay has been reported to have higher sensitivity when testing sera from humans and other species. Our objective was to determine the agreement between MN and HI assays and compare the proportion of positive samples detected by both methods in sera of mallards primary infected with the A/ mallard/MN/Sg-000169/2007(H3N8) virus and subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…According to the results shown in Figure 2 A, amino acid position 180 is located in the sialic acid binding domain as one of the receptor binding sites, suggesting that the A180V substitution might play a key role in the evolution of H9N2 viruses. A microneutralization (MN) assay was performed, which is more sensitive than the HI assay [ 36 ], to study the role of the A180V mutation in viral escape from neutralizing antibodies.
Figure 2 The decrease in the readouts of cross-MN titres due to HA A180V mutation.
…”
Section: Resultsmentioning
confidence: 99%
“…According to the results shown in Figure 2 A, amino acid position 180 is located in the sialic acid binding domain as one of the receptor binding sites, suggesting that the A180V substitution might play a key role in the evolution of H9N2 viruses. A microneutralization (MN) assay was performed, which is more sensitive than the HI assay [ 36 ], to study the role of the A180V mutation in viral escape from neutralizing antibodies.
Figure 2 The decrease in the readouts of cross-MN titres due to HA A180V mutation.
…”
Section: Resultsmentioning
confidence: 99%
“…In order to study the roles of the mutations S145N and A198V in escape from neutralizing antibodies, microneutralization (MN) assay was performed, which was more sensitive than HI assay (23). In the cross-MN assay between the F/98 strain and the virus rF/HA S145N , the virus rF/HA S145N had 4-fold lower MN titer to the anti-F/98 serum (Figure 4A), or even to the anti-rF/HA S145N serum (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the seroprevalence of antibodies to H5N1, H7N1 and H9N2 AIV subtypes was investigated by HI test, as the HI test is a well‐established standard assay for the detection of subtype‐specific AIV antibodies, and it has been shown that HI and virus neutralisation antibody titres correlate quite well (Pitisuttithum et al., 2017 ; Segovia et al., 2019 ). After heat inactivation of the sera at 56°C for 30 min, adsorption with freshly collected chicken red blood cells (RBCs) was performed to avoid non‐specific agglutination.…”
Section: Methodsmentioning
confidence: 99%
“…AIV antibodies, and it has been shown that HI and virus neutralisation antibody titres correlate quite well (Pitisuttithum et al, 2017;Segovia et al, 2019). After heat inactivation of the sera at 56 • C for 30 min, adsorption with freshly collected chicken red blood cells (RBCs) was performed to avoid non-specific agglutination.…”
Section: Haemagglutination Inhibition (Hi) Testmentioning
confidence: 99%